The Cult(ture) of the Second Sun: Remembering, Repeating, and Performing the Past Imperfect - Morimoto, Ryo (Recherches sémiotiques / Semiotic Inquiry)

(untitled) (Association canadienne de sémiotique / Canadian Semiotic Association, 2012)
This paper advances a pragmatic semiotic understanding of memory. By focusing on what is done with the real-time act of commemoration (or, the selective citation of memories), I analyze the multifunctional and multi-layered semiosis in society that presupposes and creates one’s experiential continuity between past, present, and future despite sudden (and catastrophic) change. I argue that the 2011 tsunami and ensuing nuclear meltdown in Fukushima, Japan, have unearthed parallels between the semiosis of regimentation and commemoration with regard to their interpretability, performativity, and repetitiveness. Following Parmentier, regimentation is a struggle of interpretants for the proliferation of a certain belief associated with the act of remembering/forgetting in grounding the socio-cultural continuity. I conclude by making a cautious suggestion to apply both Saussurean semiology and Peircean semiotics to study the real-time, historically represented and stochastically determined social life of signs.